“Play as a Nazi prison guard”: childhood and adolescent exposure to online extremist materials in online gaming environments - Hutchinson, Jade; Gheorghe, Ruxandra Mihaela; Yuzva Clement, David; Bell, Kenton; Kellum, Lorraine; Rana, Michaela; Shuttleworth, Alex; Scott-Smith, Stephanie (Frontiers in Psychology, 2026)
This article analyzes 18 expert assessments reflecting professional evaluations and experiences on the relationship between children, adolescents, and online gaming technologies that facilitate exposure to extremist contents and recruiters. We conducted semi-structured interviews with 18 researchers, practitioners, and policymakers from government, academic, and education-based organizations across the Indo-Pacific, Europe, and North America. Online gaming emerged as a prominent concern and important component of the sociotechnical environment that facilitates children and adolescent exposure to extremist content and recruitment activities. The findings emphasized the importance of private–public partnerships, future “safety-by-design” initiatives, interdisciplinary collaboration with the cognitive-psychological and the developmental sciences, and need to understand the swiftly changing technological characteristics of online gaming in shaping how children and adolescents may encounter online extremism. We also highlight these experts’ opinions on the wider sociotechnical environment where such exposure is made possible. This article offers guidance and recommendations to researchers, practitioners, and policymakers who wish to better understand and address the influence of online extremism on child and adolescent development in the digital age.